2017
DOI: 10.1021/acsnano.7b05796
|View full text |Cite
|
Sign up to set email alerts
|

Operando Raman Spectroscopy and Synchrotron X-ray Diffraction of Lithiation/Delithiation in Silicon Nanoparticle Anodes

Abstract: Operando Raman spectroscopy and synchrotron X-ray diffraction were combined to probe the evolution of strain in Li-ion battery anodes made of crystalline silicon nanoparticles. The internal structure of the nanoparticles during two discharge/charge cycles was evaluated by analyzing the intensity and position of Si diffraction peaks and Raman TO-LO phonons. Lithiation/delithiation of the silicon under limited capacity conditions triggers the formation of "crystalline core-amorphous shell" particles, which we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 84 publications
(122 reference statements)
1
67
0
Order By: Relevance
“…As the low Q ‐resolution associated to the experimental operando WAXS conditions did not allow to describe the asymmetrical Si 100‐ x Ge x diffraction peak shape, the SiGe (111) peak was fitted considering a single Gaussian function to obtain the time (or, equivalently, voltage) dependency of the intensity (Figure S8 in SI). We observed that, during the first lithiation, the Bragg reflection of SiGe linearly decreased in intensity, as already observed in pure Silicon nanoparticles based anodes by Tardif et al., reflecting the continuous amorphization of crystalline particles due to the alloying process. The in situ WAXS data therefore confirm that full amorphization is achieved in the Si−Ge compound, i. e. the structural and chemical heterogeneities of the core‐shell alloyed particles do not impede the lithium to penetrate to the core of the particles during lithiation .Note that there is a slope variation in the integrated intensity (indicated by the yellow arrow in Figure c) due to the corresponding increase in the current at time ∼8 hours (voltage=0.19 V).…”
Section: Resultssupporting
confidence: 86%
“…As the low Q ‐resolution associated to the experimental operando WAXS conditions did not allow to describe the asymmetrical Si 100‐ x Ge x diffraction peak shape, the SiGe (111) peak was fitted considering a single Gaussian function to obtain the time (or, equivalently, voltage) dependency of the intensity (Figure S8 in SI). We observed that, during the first lithiation, the Bragg reflection of SiGe linearly decreased in intensity, as already observed in pure Silicon nanoparticles based anodes by Tardif et al., reflecting the continuous amorphization of crystalline particles due to the alloying process. The in situ WAXS data therefore confirm that full amorphization is achieved in the Si−Ge compound, i. e. the structural and chemical heterogeneities of the core‐shell alloyed particles do not impede the lithium to penetrate to the core of the particles during lithiation .Note that there is a slope variation in the integrated intensity (indicated by the yellow arrow in Figure c) due to the corresponding increase in the current at time ∼8 hours (voltage=0.19 V).…”
Section: Resultssupporting
confidence: 86%
“…[336] The d-spacing along the (111) crystallographic plane, derived from Bragg's Law, deceased steadily upon discharging, suggesting that lithiationinduced an average compressive strain of 0.21% along the crystal plane. However, examining the stains/stresses in Si nanoparticles using the synchrotron operando XRD showed that a small tensile stress took place upon lithiation and then it was converted to the compressive stress upon delithiation, [338] as has been demonstrated in Figure 18f. I. Ali et al [337] adopted an in situ synchrotron X-ray microdiffraction to measure the stress level in Si nanowires and found that lithiation imported a compressive stress up to −325.5 MPa in the crystalline cores.…”
Section: Multibeam Optical Stress Sensor (Moss) Techniquementioning
confidence: 87%
“…2019, 9,1901810 Figure 18. [338] Copyright 2017, American Chemical Society. A peak shift took place when the graphene was strained, see the inset in the figure.…”
Section: Multibeam Optical Stress Sensor (Moss) Techniquementioning
confidence: 99%
“…Therefore, the lithiation process can be monitored by investigating the amorphization process via measuring Raman peak of crystalline Si (520.6 cm −1 ) [28] during CV measurements. In order to investigate the lithiation/delithiation process of the pristine Si and Si@ LiAlO 2 , we carried out in situ Raman measurements on electrodes while applying CV test on the half-cell simultaneously.…”
Section: Investigation Of Lithiation/delithiation Process Via In Situmentioning
confidence: 99%
“…Figure 4b,d shows the absolute intensity of c-Si peak corresponding to the first one and a half cycles performed by CV measurements of pristine Si and Si@LiAlO 2 , respectively. [28,29] In the following delithiation step, the partially recovered intensity of c-Si Raman signal indicates that the alloying process during the first lithiation is uncompleted. The drop of intensity is caused by two reasons: a) transformation of Si from crystalline into amorphous; and b) the decreasing of optical skin depth due to better conductivity with Li-Si alloy.…”
Section: Investigation Of Lithiation/delithiation Process Via In Situmentioning
confidence: 99%